Separator for electrochemical device, method for manufacturing same, and electrochemical device including same

By adjusting the bulk density of inorganic particles and adding organic fillers in the porous coating of the lithium secondary battery separator, the problem of poor dimensional stability of the separator under high temperature and humidity conditions is solved, and better heat resistance and dimensional stability are achieved.

CN119563257APending Publication Date: 2025-03-04LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480003413.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-27
Filing Date
2024-02-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The existing lithium secondary battery separators have poor dimensional stability under high temperature and humidity conditions, and the reduction of the adhesive force of the polymer binder leads to significant shrinkage of the separators.

Method used

By adjusting the bulk density of the inorganic particles in the porous coating and adding organic fillers, the weight ratio of the polymer binder and organic fillers is optimized to improve the heat resistance of the separator and the dimensional stability when impregnating the electrolyte solution.

Benefits of technology

A heat shrinkage rate of 10% or less at high temperature conditions of 130°C or higher is achieved, preventing electrode exposure caused by thermal shrinkage of the partition and improving the dimensional stability of the partition in a wet state.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005242719560000161
    Figure BDA0005242719560000161
  • Figure BDA0005242719560000162
    Figure BDA0005242719560000162
Patent Text Reader

Abstract

The present disclosure provides a separator for an electrochemical device, comprising a porous polymer substrate and a porous coating layer formed on at least one surface of the porous polymer substrate, in which the porous coating layer comprises a polymer binder, inorganic particles, and an organic filler, based on the total weight of the porous coating layer, the polymer binder is contained in an amount of 1 to 10 parts by weight, and the inorganic particles have a bulk density of 2 g / cm3 or more to 2.5 g / cm3 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application is based on and claims the benefit of priority from Korean Patent Application No. 10-2023-0026219 filed in the Korean Intellectual Property Office on February 27, 2023, the contents of which are incorporated herein by reference in their entirety.

[0002] The present disclosure relates to a separator for an electrochemical device, a method for manufacturing the same, and an electrochemical device including the same. Background Art

[0003] Electrochemical devices convert chemical energy into electrical energy using electrochemical reactions. Recently, lithium secondary batteries, which have high energy density and voltage, long cycle life, and can be used in a variety of fields, have been widely used.

[0004] The lithium secondary battery may include an electrode assembly made of a cathode, an anode and a separator disposed between the cathode and the anode, and the electrode assembly may be manufactured by being stored in a housing together with an electrolyte solution. The separator may include a porous coating comprising a polymer binder and inorganic particles on at least one surface of a porous substrate. The inorganic particles may be connected to other inorganic particles by a polymer binder to form an interstitial volume, and lithium ions may move by passing through the interstitial volume. In addition to fixing the inorganic particles, the polymer binder may also impart adhesion to the porous coating, and the porous coating may be attached to the porous substrate and the electrode, respectively.

[0005] A porous coating comprising a polymer binder and inorganic particles can prevent thermal shrinkage of a porous polymer substrate, and a separator comprising a porous coating exhibits excellent dimensional stability in a dry state without an electrolyte solution. However, in a wet state in which the separator is impregnated with an electrolyte solution, the polymer binder may be swollen by the electrolyte solution, or the adhesion of the polymer binder may deteriorate when the separator is exposed to a temperature of about 130°C or higher due to the operation of a lithium secondary battery including the separator. In this high-temperature wet state, the separator shrinks significantly as the adhesion of the porous coating decreases. In particular, since a cylindrical battery in which an electrode assembly is wound and inserted into a housing with tension applied to the electrode assembly requires a relatively small adhesion between the electrode and the separator compared to a pouch-type battery, there is a problem in which the dimensional stability in a wet state is further reduced due to the low content of the polymer binder.

[0006] Therefore, research is being conducted on separators that ensure dimensional stability under high temperature and wet conditions while maintaining a relatively low content of a polymer binder in a porous coating layer. Summary of the invention

[0007] Technical issues

[0008] An object of the present disclosure is to provide a separator for an electrochemical device having excellent heat resistance and improved shrinkage in a state of being impregnated with an electrolyte solution by adjusting the packing density of inorganic particles contained in a porous coating layer and further containing an organic filler.

[0009] Technical Solution

[0010] One aspect of the present disclosure provides a separator for an electrochemical device, comprising a porous polymer substrate and a porous coating formed on at least one surface of the porous polymer substrate, wherein the porous coating comprises a polymer binder, inorganic particles, and an organic filler, the polymer binder being included in an amount of 1 to 10 parts by weight based on the total weight of the porous coating, and the inorganic particles having a packing density of 2 g / cm 3 or greater up to 2.5g / cm 3 or smaller.

[0011] The organic filler may be one or more selected from the following: polyethylene, polyacetal, polysulfone (PSF), polyethersulfone (PES), polyetherimide (PEI), polyphenylene sulfide (PPS), polyetheretherketone (PEEK), polycarbonate, polyamideimide (PAI), polyimide (PI), polyamide, polyphenylene ether, polybutylene terephthalate and polyethylene terephthalate.

[0012] The polymer binder and the organic filler may be included in a weight ratio of 5:1 to 1:5.

[0013] The polymer binder may be one or more selected from the following: polyacrylic acid, polyacrylamide, methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, ethylhexyl acrylate, methyl methacrylate, styrene-butadiene rubber, nitrile rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, and copolymers containing one or more thereof.

[0014] The polymer binder may have a weight average molecular weight of 100,000 to 500,000.

[0015] The bulk density of inorganic particles can be 2.1 g / cm 3 or greater up to 2.3g / cm 3 or smaller.

[0016] Another aspect of the present disclosure provides an electrochemical device as an electrochemical device including a cathode, an anode, and a separator disposed between the cathode and the anode, wherein the separator is another separator for an electrochemical device in one aspect.

[0017] The electrochemical device may be a lithium secondary battery.

[0018] The electrochemical device may further include an electrolyte solution including EC / EMC at a weight ratio of 3 / 7.

[0019] Beneficial Effects

[0020] The separator for an electrochemical device according to the present disclosure can provide improved dimensional stability in a wet state impregnated with an electrolyte solution. Specifically, the separator can exhibit a thermal shrinkage rate of 10% or less in the TD direction under high temperature conditions of 130° C. or higher, thereby preventing electrode exposure due to thermal shrinkage of the separator. DETAILED DESCRIPTION

[0021] Hereinafter, each configuration of the present disclosure will be described in more detail so that those skilled in the art to which the present disclosure belongs can easily implement each configuration of the present disclosure. However, this is only an example, and the scope of rights of the present disclosure is not limited by the following content.

[0022] The term "comprising" as used in this specification is used to list materials, compositions, devices and methods useful in the present disclosure and is not limited to the listed examples.

[0023] The terms "about" and "substantially" used in this specification are used to mean a range of values ​​or degrees or their approximations by taking into account unique manufacturing and material tolerances, and are used to prevent an infringer from unfairly using the disclosure in which precise values ​​or absolute values ​​provided to aid understanding of the disclosure are mentioned.

[0024] The term "electrochemical device" used in this specification may mean a primary battery, a secondary battery, a supercapacitor, or the like.

[0025] The term “wet state” used in the present specification may mean a state in which the separator is impregnated with at least a part of the electrolyte solution.

[0026] One embodiment of the present disclosure provides a separator for an electrochemical device, comprising a porous polymer substrate and a porous coating layer formed on at least one surface of the porous polymer substrate, wherein the porous coating layer comprises a polymer binder, inorganic particles, and an organic filler, the polymer binder being included in an amount of 1 to 10 parts by weight based on the total weight of the porous coating layer, and the inorganic particles having a packing density of 2 g / cm 3 or greater up to 2.5g / cm 3 or smaller.

[0027] The porous polymer substrate is a porous film having a plurality of pores formed therein, and can electrically insulate the cathode and the anode to prevent short circuits. For example, when the electrochemical device is a lithium secondary battery, the porous polymer substrate can be an ion-conducting barrier that allows lithium ions to pass through while blocking electrical contact between the cathode and the anode. At least some of the pores can form a three-dimensional network that is connected to the surface and interior of the porous polymer substrate, and a fluid can pass through the porous polymer substrate through the pores.

[0028] The porous polymer substrate can use a material that is physically and chemically stable to an electrolyte solution that is an organic solvent. For example, the porous polymer substrate may include a resin, such as a polyolefin-based resin (e.g., polyethylene, polypropylene, and polybutylene), polyvinyl chloride, polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyamideimide, nylon, polytetrafluoroethylene, and copolymers or mixtures thereof, but is not limited thereto. Preferably, a polyolefin-based resin can be used. Polyolefin-based resins can be processed into relatively thin thicknesses and are easy to apply slurry for coating, making them suitable for manufacturing electrochemical devices with higher energy density.

[0029] The porous polymer substrate may have a monolayer or multilayer structure. The porous polymer substrate may provide a shutdown function in the case of a high temperature runaway of the battery by including two or more polymer resin layers with different melting points (Tm). For example, the porous polymer substrate may include a polypropylene layer with a relatively high melting point and a polyethylene layer with a relatively low melting point. Preferably, the porous polymer substrate may be a three-layer structure in which polypropylene, polyethylene and polypropylene are laminated in this order. As the temperature of the battery rises to a predetermined temperature or higher, the polyethylene layer may prevent thermal runaway of the battery by closing the pores when melting.

[0030] The thickness of the porous polymer substrate may be 1 μm or more to 100 μm or less. Specifically, the thickness of the porous polymer substrate may be 10 μm or more to 90 μm or less, 20 μm or more to 80 μm or less, 30 μm or more to 70 μm or less, or 40 μm or more to 60 μm or less. Preferably, the thickness of the polymer substrate may be 1 μm or more to 30 μm or less. More preferably, the thickness of the polymer substrate may be 5 μm or more to 15 μm or less, or 8 μm or more to 13 μm or less. By adjusting the thickness of the porous polymer substrate within the above range, the amount of active material contained in the electrochemical device may be increased by minimizing the volume of the electrochemical device while electrically insulating the cathode and anode.

[0031] The porous polymer substrate may include pores having an average diameter of 0.01 μm or more to 1 μm or less. Specifically, the size of the pores included in the porous polymer substrate may be 0.01 μm or more to 0.09 μm or less, 0.02 μm or more to 0.08 μm or less, 0.03 μm or more to 0.07 μm or less, or 0.04 μm or more to 0.06 μm or less. Preferably, the size of the pores may be 0.02 μm or more to 0.06 μm or less. By adjusting the pore size of the porous polymer substrate within the above range, the air permeability and ionic conductivity of the entire separator to be manufactured may be adjusted.

[0032] The air permeability of the porous polymer substrate can be 10 seconds / 100cc or more to 100 seconds / 100cc or less. Specifically, the air permeability of the porous polymer substrate can be 10 seconds / 100cc or more to 90 seconds / 100cc or less, 20 seconds / 100cc or more to 80 seconds / 100cc or less, 30 seconds / 100cc or more to 70 seconds / 100cc or less, or 40 seconds / 100cc or more to 60 seconds / 100cc or less. Preferably, the air permeability of the porous polymer substrate can be 50 seconds / 100cc or more to 70 seconds / 100cc or less. When the air permeability of the porous polymer substrate is within the above range, the air permeability of the separator to be manufactured can be set within the range suitable for ensuring the output and cycle characteristics of the electrochemical device.

[0033] Air permeability (seconds / 100cc) means the time (seconds) it takes for 100cc of air to pass through a porous polymer substrate or separator of a predetermined area under a certain pressure. Air permeability can be measured using an air permeability tester (Gurley Density Tester) according to ASTM D726-58, ASTM D726-94, or JIS-P8117. For example, Gurley's 4110N instrument can be used to measure the pressure of 0.304kPa air or 1.215kN / m 2 100cc of air moves through 1 square inch (or 6.54cm) under water pressure. 2 ) of a sample. For example, the EG01-55-1MR instrument from Asahi Seico can be used to measure the time it takes for 100cc of air to pass through a 1 square inch sample at room temperature under a constant pressure of 4.8 inches of water.

[0034] The porosity of the porous polymer substrate can be 10 volume % or more to 60 volume % or less. Specifically, the porosity of the porous polymer substrate can be 15 volume % or more to 55 volume % or less, 20 volume % or more to 50 volume % or less, 25 volume % or more to 45 volume % or less, or 30 volume % or more to 40 volume % or less. Preferably, the porosity of the porous polymer substrate can be 30 volume % or more to 50 volume % or less. When the porosity of the porous polymer substrate is within the above range, the ionic conductivity of the separator to be manufactured can be set within a range suitable for ensuring the output and cycle characteristics of the electrochemical device.

[0035] Porosity means the volume ratio of the pores of a porous polymer substrate to the total volume. Porosity can be measured by methods known in the art. For example, it can be measured by the BrunauerEmmettTeller (BET) measurement method using nitrogen adsorption, a capillary flow porosimeter, water or mercury penetration method.

[0036] The porous coating layer is formed on at least any one surface of the porous polymer substrate and comprises a polymer binder, inorganic particles and an organic filler. The porous coating layer can be formed by coating a coating slurry comprising a polymer binder, inorganic particles, an organic filler and a dispersion medium on at least one surface of the porous polymer substrate. While allowing lithium ions to pass there through the interstitial volume in which the inorganic particles are connected by the polymer binder, the porous coating layer is attached to the porous polymer substrate, thereby preventing thermal shrinkage of the porous polymer substrate.

[0037] The coating slurry can include a dispersion medium, so that at least a portion of the polymer binder and the organic filler are dissolved or dispersed and the inorganic particles are dispersed. The coating slurry can use a coating slurry in which the polymer binder, the inorganic particles and the organic filler are uniformly dispersed by adjusting the type and content of the dispersion medium. For example, the dispersion medium can be selected from one of the following: water, ethanol, acetone, isopropyl alcohol (IPA), dimethylacetamide (DMAc), dimethylformamide (DMF), N-methyl-2-pyrrolidone (NMP), acetonitrile, and combinations thereof. Preferably, the dispersion medium can be NMP. By using the above-mentioned type of dispersion medium, a porous coating layer uniformly dispersed with polymer binders and inorganic particles can be formed.

[0038] By further including additives such as dispersants, surfactants, defoamers and flame retardants, the coating slurry can improve dispersibility and flame retardancy and improve the uniformity of the porous coating to be formed. For example, the dispersant may include one or more selected from the following: polyacrylic acid, oil-soluble polyamines, oil-soluble amine compounds, fatty acids, fatty alcohols, sorbitan fatty acid esters, tannic acid and pyrogallic acid. By using the above-mentioned type of dispersant, the stability of the coating slurry can be improved, and the uniformity of the porous coating to be formed by the coating slurry can be ensured.

[0039] Based on the total weight of the coating slurry, the additive may be included in an amount of 0 wt % or more to 5 wt % or less. Specifically, the additive may be included in an amount of 0.01 wt % or more to 4 wt % or less, 0.1 wt % or more to 3 wt % or less, or 1 wt % or more to 2 wt % or less. Preferably, the content of the additive may be 1 wt % or more to 5 wt % or less. By adjusting the content of the additive within the above range, uniform dispersion and stability of the inorganic particles contained in the coating slurry can be achieved.

[0040] After forming the porous coating, the dispersion medium contained in the coating slurry can be removed by drying or heating. For example, the porous coating can contain 5ppm or less dispersion medium. Preferably, the porous coating can be composed of a polymer binder and inorganic particles. In the process of removing the dispersion medium, a plurality of holes can be formed on and inside the porous coating surface. The hole can include a gap volume formed between the inorganic particles, and can have a structure that a fluid can pass through by forming a three-dimensional network.

[0041] The thickness of the porous coating layer may be 1 μm or more to 15 μm or less. Specifically, the thickness of the porous coating layer may be 2 μm or more to 14 μm or less, 3 μm or more to 13 μm or less, 4 μm or more to 12 μm or less, 5 μm or more to 11 μm or less, 6 μm or more to 10 μm or less, or 7 μm or more to 9 μm or less. Preferably, the thickness of the porous coating layer may be 1 μm or more to 5 μm or less, more preferably, 1 μm or more to 3 μm or less. By adjusting the thickness of the porous coating layer within the above range, the shrinkage of the porous polymer substrate can be minimized, and stable adhesion to the porous polymer substrate can be achieved.

[0042] The polymer binder may bind the inorganic particles contained in the porous coating layer and impart adhesive force to the porous coating layer.The polymer binder may have a spherical shape or an elliptical shape, but may be meant to include other shapes except for the amorphous shape.

[0043] The polymer binder may include an acrylic binder. For example, the polymer binder may be one or more selected from the following: polyacrylic acid, polyacrylamide, methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, ethylhexyl acrylate, methyl methacrylate, styrene-butadiene rubber, nitrile rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, and copolymers comprising one or more thereof. Acrylic binders combine inorganic particles to form a network structure and may exhibit adhesion to porous polymer substrates and electrodes. Preferably, the polymer binder may include a copolymer of polyacrylic acid and polyacrylamide. The polymer binder may be swollen by an electrolyte solution, reducing bonding strength. However, the copolymer of polyacrylic acid and polyacrylamide has low swelling caused by an electrolyte solution and is heat-resistant, so the separator comprising the copolymer may have improved thermal shrinkage in a wet state.

[0044] The weight average molecular weight of the polymer binder may be 100,000 to 500,000. Specifically, the weight average molecular weight of the polymer binder may be 150,000 or more to 450,000 or less, 200,000 or more to 400,000 or less, or 250,000 or more to 350,000 or less. Preferably, the weight average molecular weight of the polymer binder may be 100,000 to 300,000. By adjusting the weight average molecular weight of the polymer binder within the above range, the thermal shrinkage of the separator containing it can be improved by reducing the swelling of the polymer binder due to the electrolyte solution.

[0045] The weight average molecular weight can be measured by gel permeation chromatography (GPC) (PL GPC220, Agilent Technologies). For example, the weight average molecular weight can be measured by using trichlorobenzene (TCB) as a solvent in a PL Olexis (Polymer Laboratories) column (column temperature is 160° C.) and using an Agilent high temperature RI detector under conditions such as a sample concentration of 1.0 mg / mL, a flow rate of 1.0 mL / min, and an injection volume of 200 μl (standard: polystyrene).

[0046] Based on the gross weight of the porous coating, the porous coating may include 1 to 10 parts by weight of a polymer binder. Specifically, the porous coating may include a polymer binder in an amount of 1 to 9 parts by weight or less, 2 to 8 parts by weight or less, 3 to 7 to 6 parts by weight or less, or 4 to 6 parts by weight or less. Preferably, the porous coating may include 1 to 5 parts by weight of a polymer binder. If the content of the polymer binder is less than 1 part by weight, it is impossible to form a gap volume by combining between inorganic particles, making it difficult to transfer lithium ions, thereby increasing the resistance of the separator. If the content of the polymer binder exceeds 10 parts by weight, the amount of the polymer binder swollen by the electrolyte solution increases, and the porous coating may be peeled off from the porous polymer substrate.

[0047] The organic filler is a polymer resin having a melting point (Tm) or a glass transition temperature (Tg) of 100° C. or higher, and can prevent the separator from shrinking when in a high temperature wet state by imparting heat resistance properties to the porous coating. For example, the organic filler can be one or more selected from the following: polyethylene, polyacetal, polysulfone, polyethersulfone, polyetherimide, polyphenylene sulfide, polyetheretherketone, polycarbonate, polyamideimide, polyimide, polyamide, polyphenylene oxide, polybutylene terephthalate, and polyethylene terephthalate. Preferably, the organic filler can be one or more selected from the following: polyethylene, polysulfone, polyethersulfone, polyimide, and polyamideimide.

[0048] The polymer binder and the organic filler may be contained in the porous coating layer in a weight ratio of 5:1 to 1:5. Specifically, the weight ratio of the polymer binder and the organic filler may be 4:1 to 1:4, 3:1 to 1:3, 2:1 to 1:2, or 1:1. Preferably, the weight ratio of the polymer binder and the organic filler may be 2:1 to 1:2. When the content of the polymer binder and the organic filler is adjusted to the above range, the adhesion and heat resistance of the porous coating layer are simultaneously ensured, so that a separator with reduced thermal shrinkage can be obtained even in a wet state at a high temperature wet state.

[0049] The porous coating layer may include a polymer binder and inorganic particles in a weight ratio of 5:95 to 80:20. Specifically, the weight ratio of the polymer binder and the inorganic particles in the porous coating layer may be 10:90 to 80:20, 20:80 to 80:20, 30:70 to 70:30, 40:60 to 60:40, or 50:50. Preferably, the weight ratio of the polymer binder and the inorganic particles may be 60:40 to 80:20. By adjusting the composition of the porous coating layer within the above range, the adhesive force of the separator and the dimensional stability under high temperature and wet conditions may be ensured at the same time.

[0050] Inorganic particles can be those that are electrochemically stable. There are no particular limitations on the inorganic particles, as long as no oxidation and / or reduction reactions occur within the operating voltage range of the electrochemical device (e.g., based on Li / Li + , 0 to 5 V). In particular, when inorganic particles with a high dielectric constant are used as the inorganic particles, the ionic conductivity of the electrolyte solution can be improved by contributing to increasing the degree of dissociation of the electrolyte salt (e.g., a lithium salt) in the liquid electrolyte. For the above reasons, the inorganic particles preferably include high dielectric constant inorganic particles having a dielectric constant of 5 or greater, preferably 10 or greater. Non-limiting examples of inorganic particles having a dielectric constant of 5 or greater include BaTiO3, Pb(Zr,Ti)O3 (PZT), b 1- x La x Zr 1-y Ti y O3 (PLZT, 0 < x < 1, 0 < y < 1), Pb(Mg 1 / 3 Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium oxide (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, SiO2, Y2O3, Al2O3, Al(OH)3, SiC, AlOOH, TiO2, or a mixture thereof.

[0051] In addition, inorganic particles having the ability to transfer lithium ions (i.e., inorganic particles containing lithium element but having the function of moving lithium ions without storing lithium) can be used as the inorganic particles. Non-limiting examples of inorganic particles having lithium ion transfer ability include (LiAlTiP) x O y series glasses (0 < x < 4, 0 < y < 13), such as lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), 14Li2O-9Al2O3-38TiO2-39P2O5, etc.; lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), such as lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), Li 3.25Ge 0.25 P 0.75 S4 etc.; lithium nitrides (Li x N y , 0 < x < 4, 0 < y < 2), such as Li3N etc.; SiS2 series glasses (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), such as Li3PO4 - Li2S - SiS2 etc.; P2S5 series glasses (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7), such as LiI - Li2S - P2S5 etc.; or mixtures thereof.

[0052] In addition, the inorganic particles are inorganic particles having flame retardancy, and inorganic particles that can impart flame retardant properties to the separator or prevent a rapid increase in temperature inside the electrochemical device can be used as the inorganic particles. Non - limiting examples of the inorganic particles having flame retardancy include Sb2O3, Sb2O4, Sb2O5, SrTiO3, SnO2, CeO2, MgO, Mg(OH)2, NiO, CaO, ZnO, Zn2SnO4, ZnSnO3, ZnSn(OH)6, ZrO2, Y2O3, SiO2, Al2O3, AlOOH, Al(OH)3, SiC, TiO2, H3BO3, HBO2, and mixtures thereof.

[0053] The average particle size (D50) of the inorganic particles can be 50 nm or more to 5,000 nm or less. Specifically, the average particle size (D50) of the inorganic particles can be 100 nm or more to 4,500 nm or less, 200 nm or more to 4,000 nm or less, 300 nm or more to 3,000 nm or less, 400 nm or more to 2,000 nm or less, or 500 nm or more to 1,000 nm or less. If the average particle size of the inorganic particles is less than 50 nm, then as the specific surface area increases, additional polymer binder is required for the bonding between the inorganic particles, which is disadvantageous in terms of resistance. If the average particle size of the inorganic particles exceeds 5,000 nm, the uniformity of the coating surface may be reduced, and damage to the porous polymer substrate or the electrode may occur during lamination.

[0054] The aspect ratio of inorganic particles can be 1 or more to 2 or less. Specifically, the aspect ratio of inorganic particles can be 1.1 or more to 1.9 or less, 1.2 or more to 1.8 or less, 1.3 or more to 1.7 or less, or 1.4 or more to 1.6 or less. Preferably, the aspect ratio of inorganic particles can be 1.5 or more to 1.8 or less. The aspect ratio of inorganic particles is adjusted within the above range, so the movement of the polymer binder through the holes between the inorganic particles is promoted, and a porous coating in which the film-forming region is uniformly distributed by the formation of the film-forming region after the movement of the polymer binder can be formed.

[0055] The BET specific surface area of ​​inorganic particles can be 5m 2 / g or greater up to 25m 2 / g or less. Specifically, the BET specific surface area of ​​the inorganic particles can be 6m 2 / g or greater up to 24m 2 / g or less, 7m 2 / g or greater up to 23m 2 / g or less, 8m 2 / g or greater up to 22m 2 / g or less, 9m 2 / g or greater up to 21m 2 / g or less, 10m 2 / g or greater up to 20m 2 / g or less, 11m 2 / g or greater up to 19m 2 / g or less, 12m 2 / g or greater up to 18m 2 / g or less, 13m 2 / g or greater up to 17m 2 / g or less, or 14m 2 / g or greater up to 26m 2 By adjusting the BET specific surface area of ​​the inorganic particles within the above range, the movement of the polymer binder through the pores between the inorganic particles can be adjusted.

[0056] The bulk density of inorganic particles can be 2g / cm 3 or greater up to 2.5g / cm 3 The bulk density is based on the porous coating layer formed after the coating slurry is applied and dried. Specifically, the bulk density of the inorganic particles may be 2.1 g / cm 3 or greater up to 2.4g / cm 3 or less, or 2.2g / cm 3 or greater up to 2.3g / cm 3Preferably, the bulk density of the inorganic particles can be 2.1 g / cm 3 or greater up to 2.3g / cm 3 If the bulk density of the inorganic particles is less than 2 g / cm 3 , as the separator shrinks in a high temperature and wet state, the electrodes are exposed. If the packing density of the inorganic particles exceeds 2.5 g / cm 3 , the air permeability and resistance of the separator increase, making it impossible to ensure stable cycle characteristics.

[0057] The air permeability of the separator for electrochemical device can be 20 seconds / 100cc or more to 90 seconds / 100cc or less. Specifically, the air permeability of the separator can be 25 seconds / 100cc or more to 85 seconds / 100cc or less, 30 seconds / 100cc or more to 80 seconds / 100cc or less, 35 seconds / 100cc or more to 75 seconds / 100cc or less, 40 seconds / 100cc or more to 70 seconds / 100cc or less, 45 seconds / 100cc or more to 65 seconds / 100cc or less, or 50 seconds / 100cc or more to 55 seconds / 100cc or less. Preferably, the air permeability of the separator can be 80 seconds / 100cc or more to 90 seconds / 100cc or less. When the air permeability of the separator is within the above range, the output, stability and cycle characteristics of the electrochemical device can be ensured.

[0058] When a battery is manufactured using the separator for an electrochemical device, the resistance of the battery may be 0.5 ohm or more to 1.5 ohm or less. Specifically, the resistance of the battery may be 0.6 ohm or more to 1.4 ohm or less, 0.7 ohm or more to 1.3 ohm or less, 0.8 ohm or more to 1.2 ohm or less, or 0.9 ohm or more to 1.1 ohm or less. Preferably, the resistance of the battery may be 0.6 ohm or more to 0.8 ohm or less.

[0059] Another embodiment of the present disclosure provides a method for manufacturing a separator for an electrochemical device, comprising the steps of: forming a coating by coating at least one surface of a porous polymer substrate with a coating slurry comprising a polymer binder, inorganic particles, an organic filler, and a dispersion medium, and drying the coating to remove the dispersion medium. Contents repeated with those described in the above separator for an electrochemical device are replaced by the description of the aforementioned embodiment.

[0060] The step of forming the coating is to coat at least one surface of the porous polymer substrate with a coating slurry comprising a polymer binder, inorganic particles, an organic filler and a dispersion medium. For example, the coating can be formed by methods such as rod coaters, wire rod coaters, roller coaters, spray coaters, spin coaters, inkjet coaters, screen coaters, reverse coaters, gravure coaters, blade coaters, slot die coaters, hot melt coaters, comma coaters and direct metering coaters, but is not limited thereto. Preferably, the step of forming the coating can use a rod coater or a slot die coater to coat both surfaces of the porous polymer substrate simultaneously with a coating slurry.

[0061] The step of forming the coating may also include a step of corona discharge treating at least one surface of the porous polymer substrate. After the corona discharge treating step, the coating slurry may be applied to the porous polymer substrate. The step of corona discharge treating at least one surface of the porous polymer substrate may prevent the bonding force between the surface of the porous polymer substrate and the surface of the coating from being reduced at high temperatures, and prevents the bonding force between the surface of the polymer substrate and the surface of the coating from being reduced by the electrolyte.

[0062] Corona discharge treatment can be for processing at least one surface of porous polymer substrate with 0.1kV or more to 10kV or less voltage in air. Specifically, corona discharge treatment can be for processing with 0.2kV or more to 9kV or less, 0.3kV or more to 8kV or less, 0.4kV or more to 7kV or less, 0.5kV or more to 6kV or less, 0.6kV or more to 5kV or less, 0.7kV or more to 4kV or less, 0.8kV or more to 3kV or less, 0.9kV or more to 2kV or less or 1.0kV or more to 2kV or less voltage in air. Preferably, corona discharge treatment can be for processing with 1.8kV voltage in air. The applied voltage of corona discharge treatment is adjusted in the above range, so the functional group of appropriate number can be formed on the surface of polymer substrate, and the damage to the surface of polymer substrate can be prevented.

[0063] The step of removing the dispersion medium may be drying or heating the coating to evaporate the dispersion medium contained in the coating. The step of removing the dispersion medium may be performed at a temperature capable of evaporating only the dispersion medium contained in the coating without deforming the polymer binder contained in the coating. For example, the step of removing the dispersion medium may be heating the coating to a predetermined temperature, but ensuring that the temperature of the coating surface does not exceed 60° C. When the coating is heated under the above conditions, the thermal energy is first used to heat the dispersion medium to cause a phase change, and may not be used to change the polymer binder.

[0064] Another embodiment of the present disclosure provides an electrochemical device, including a cathode, an anode and a separator inserted between the cathode and the anode, wherein the separator is a separator for an electrochemical device of the above embodiment. The electrochemical device can be manufactured by inserting an electrode assembly including a cathode, an anode and a separator inserted between the cathode and the anode into a housing or a bag and sealing it. Before the housing or bag is sealed, the electrode assembly can be impregnated with an electrolyte solution by injecting an electrolyte solution. The shape of the housing or bag is not limited. For example, the electrochemical device can be a cylindrical, prismatic, coin-shaped or pouch-shaped lithium secondary battery.

[0065] The cathode and anode can be coated by applying an electrode active material on at least one surface of each current collector and drying. A material having conductivity while not causing chemical changes in the electrochemical device can be used as a current collector. For example, current collectors for cathodes include aluminum, nickel, titanium, fired carbon, and stainless steel; and surfaces of aluminum or stainless steel treated with carbon, nickel, titanium, silver, etc., but are not limited thereto. For example, current collectors for anodes include copper, nickel, titanium, fired carbon, and stainless steel; and surfaces of copper or stainless steel treated with carbon, nickel, titanium, silver, etc., but are not limited thereto. The current collector can be in a variety of forms, such as thin metal plates, films, foils, meshes, porous bodies, or foams.

[0066] The cathode includes a cathode current collector and a cathode active material layer containing a cathode active material, a conductive material and a binder resin on at least one surface of the current collector. The cathode active material may include one or a mixture of two or more of the following: a layered compound such as lithium manganese composite oxide (LiMn2O4, LiMnO2, etc.), lithium cobalt oxide (LiCoO2), or lithium nickel oxide (LiNiO2), and a compound substituted by one or more transition metals; a compound having the formula Li 1+x Mn 2-x Lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2, etc.; lithium copper oxides (Li2CuO2); vanadium oxides such as LiV3O8, LiV3O4, V2O5, Cu2V2O7, etc.; LiNi 1-x M x Ni-site lithium nickel oxide represented by O2 (wherein M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); represented by the chemical formula LiMn 1-x M xA lithium manganese composite oxide represented by O2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li2Mn3MO8 (where M = Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of Li in the formula is replaced by an alkaline earth metal ion; a disulfide compound; and Fe2(MoO4)3.

[0067] The anode includes an anode current collector and an anode active material layer containing an anode active material, a conductive material, and a binder resin on at least one surface of the current collector. The anode may contain, as the anode active material, one or a mixture of two or more selected from the following: carbon, such as lithium metal oxide, non-graphitizable carbon, and graphitic carbon; silicon-based materials, such as LixFe2O3 (0 ≤ x ≤ 1), Li x WO2 (0 ≤ x ≤ 1), Si, SiO x (0 < x < 2), SiC, and Si alloys; metal composite oxides, such as Sn x Me 1-x Me' y O z (Me: Mn, Fe, Pb, and Ge; Me': Al, B, P, Si, elements of Groups 1, 2, and 3 of the periodic table, and halogens; 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8), etc.; lithium metal; lithium alloys; tin-based alloys; metal oxides, such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers, such as polyacetylene; Li-Co-Ni-based materials; and titanium oxides.

[0068] The conductive material may be any one selected from the following: graphite, carbon black, carbon fiber or metal fiber, metal powder, conductive whisker, conductive metal oxide, carbon nanotube, activated carbon, and polyphenylene derivative, or a mixture of two or more of these conductive materials. The carbon nanotube has a diameter with nanoscale dimensions and sp 2The carbon nanotube is a cylindrical graphite sheet with a bonding structure, and exhibits conductor or semiconductor properties according to the angle and structure of the graphite sheet winding. According to the number of bonds forming the wall, carbon nanotubes can be divided into single-walled carbon nanotubes (SWCNT), double-walled carbon nanotubes (DWCNT) and multi-walled carbon nanotubes (MWCNT), and these carbon nanotubes can be appropriately selected according to the purpose of dispersion. More specifically, the carbon nanotube can be one selected from the following: natural graphite, artificial graphite, super-p, acetylene black, Ketjen black, channel black, furnace black, lamp black, summer black, Denka black, aluminum powder, nickel powder, zinc oxide, potassium titanate and titanium oxide, or a mixture of two or more conductive materials thereof.

[0069] The binder resin commonly used for the electrode of the electrochemical device can be used as the binder resin. The non-limiting examples of such binder resins can include polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer (polyethylene-co-vinyl acetate), polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan and carboxymethyl cellulose, but are not limited thereto.

[0070] The electrolyte solution is a + B - The salts of the same structure, and A + Contains alkali metal cations (such as Li + 、Na + , K + , or a combination thereof), and B - Contains anions (such as PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、C(CF2SO2)3 -, or a combination thereof) is dissolved or dissociated in an organic solvent consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma-butyrolactone (γ-butyrolactone), or a mixture thereof, but is not limited thereto.

[0071] The electrochemical device including the electrode assembly may be a lithium secondary battery. The battery may be used as a unit cell, and may be used as a battery module including a unit cell, a battery pack including a battery module, and a device including a battery pack as a power source. The device may include small-sized devices such as computers, mobile phones, and power tools; medium-sized to large-sized devices such as electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV) driven and moved by electric motors; electric two-wheeled vehicles including electric bicycles (E-bike) and electric scooters (E-scooters); electric golf carts; and energy storage systems, but are not limited thereto.

[0072] Hereinafter, the present disclosure will be described in more detail through specific embodiments and experimental examples. The following embodiments and experimental examples are intended to illustrate the present disclosure, and the present disclosure is not limited by the following embodiments and experimental examples.

[0073] Example 1

[0074] Preparation of coating slurry

[0075] A coating slurry in which a polymer binder, inorganic particles and an organic filler are dispersed was prepared by mixing an acrylic polymer binder (a copolymer in which polyacrylic acid and polyacrylamide are copolymerized at a ratio of 50:50, Mw: 300,000) and an organic filler (polyethylene particles) in a weight ratio of 2:1 in 100 mL of distilled water at room temperature (25° C.), adding 20 g of inorganic particles (Al2O3, aspect ratio: 1.5:1, particle size: 500 nm), and stirring with an oscillator for 60 minutes.

[0076] Preparation of porous substrates

[0077] A polyethylene film (MI: 0.2 g / 10 min, T m : 135°C, porosity: 45%, average pore size: 45 nm) as the porous substrate.

[0078] Manufacturing of separators

[0079] The coating slurry was coated on both surfaces of a polyethylene film using a bar coater to form porous coating layers each having a coating thickness of 2 μm.

[0080] The porous coating layer was prepared by repeating the following process five times, wherein the inorganic particles contained in the porous coating layer had a bulk density of 2.0 g / cm 3 and a separator having a total thickness of 13 μm: a low-temperature air volume was applied to the polyethylene film on which the porous coating layer was formed, and the porous coating layer was dried while controlling the surface temperature thereof not to exceed 60° C. to remove the dispersion medium.

[0081] Example 2

[0082] The separator was manufactured in the same manner as in Example 1 above, except that the bulk density of the inorganic particles was adjusted to 2.5 g / cm by adjusting the solid content when preparing the coating slurry. 3 .

[0083] Example 3

[0084] A separator was manufactured in the same manner as in Example 1 above, except that the polymer binder and the organic filler were mixed at a weight ratio of 1:2 when preparing the coating slurry.

[0085] Example 4

[0086] A separator was manufactured in the same manner as in Example 1 above, except that the polymer binder and the organic filler were mixed at a weight ratio of 5:1 when preparing the coating slurry.

[0087] Comparative Example 1

[0088] A separator was manufactured in the same manner as in Example 1 above, except that no organic filler was used in preparing the coating slurry.

[0089] Comparative Example 2

[0090] A separator was manufactured in the same manner as in Example 1 above, except that the polymer binder and the organic filler were mixed at a weight ratio of 6:1 when preparing the coating slurry.

[0091] Comparative Example 3

[0092] A separator was manufactured in the same manner as in Example 1 above, except that the polymer binder and the organic filler were mixed at a weight ratio of 1:6 when preparing the coating slurry.

[0093] Comparative Example 4

[0094] The separator was manufactured in the same manner as in Example 1 above, except that the bulk density of the inorganic particles was adjusted to 1.5 g / cm by adjusting the solid content when preparing the coating slurry. 3 .

[0095] Comparative Example 5

[0096] The separator was manufactured in the same manner as in Example 1 above, except that the bulk density of the inorganic particles was adjusted to 3.0 g / cm by adjusting the solid content when preparing the coating slurry. 3 .

[0097] Experimental example: Checking the physical properties of the separator

[0098] Air permeability measurement

[0099] The air permeability of 100cc was measured using a Gurley densometer (Gurley, 4110N) with a diameter of 28.6mm and a diameter of 645mm. 2 The time the area of ​​the separator spends is a measure of the air permeability.

[0100] Check dimensional stability

[0101] Separators of the embodiments and comparative examples with a size of 5 cm×5 cm were prepared and each was inserted into an aluminum bag with a size of 7 cm×10 cm. 1 g of electrolyte solution was injected into the bag and the bag was sealed. The following solvent was used as the electrolyte solution: it had ethylene carbonate (EC) / ethyl methyl carbonate (EMC) mixed in a weight ratio of 3 / 7 and contained 3 mol of vinyl carbonate (VC), 1.5 mol of propane sultone (PS), 1 mol of ethylene sulfate (ESa) and 1 mol of lithium salt LiPF6 as additives.

[0102] After the sealed bags were exposed to an oven at 135° C. for 30 minutes, the bags were opened and the shrinkage in the TD direction was measured and shown in Tables 1 and 2 below.

[0103] [Table 1]

[0104]

[0105] [Table 2]

[0106]

Claims

1. A separator for an electrochemical device, comprising a porous polymer substrate and a porous coating formed on at least one surface of the porous polymer substrate, wherein the porous coating comprises a polymer binder, inorganic particles and an organic filler, The polymer binder is included in an amount of 1 part by weight to 10 parts by weight based on the total weight of the porous coating layer, and The bulk density of the inorganic particles is 2 g / cm 3 or greater up to 2.5g / cm 3 or smaller.

2. The separator for an electrochemical device according to claim 1, wherein the organic filler is one or more selected from the group consisting of polyethylene, polyacetal, polysulfone (PSF), polyethersulfone (PES), polyetherimide (PEI), polyphenylene sulfide (PPS), polyetheretherketone (PEEK), polycarbonate, polyamideimide (PAI), polyimide (PI), polyamide, polyphenylene ether, polybutylene terephthalate and polyethylene terephthalate. 3 . The separator for an electrochemical device according to claim 1 , wherein the polymer binder and the organic filler are contained in a weight ratio of 5:1 to 1:

5.

4. The separator for an electrochemical device according to claim 1, wherein the polymer binder is one or more selected from the group consisting of polyacrylic acid, polyacrylamide, methyl acrylate, ethyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, ethylhexyl acrylate, methyl methacrylate, styrene-butadiene rubber, nitrile rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, and copolymers comprising one or more thereof. 5 . The separator for an electrochemical device according to claim 4 , wherein the polymer binder has a weight average molecular weight of 100,000 to 500,000.

6. The separator for an electrochemical device according to claim 1, wherein the bulk density of the inorganic particles is 2.1 g / cm 3 or greater up to 2.3g / cm 3 or smaller. 7 . A separator for an electrochemical device, comprising a cathode, an anode, and a separator provided between the cathode and the anode as an electrochemical device, wherein the separator is the separator for an electrochemical device according to claim 1 . 8 . The separator for an electrochemical device according to claim 8 , wherein the electrochemical device further comprises an electrolyte solution comprising EC / EMC at a weight ratio of 3 / 7.

Citation Information

Patent Citations

  • A negative electrode for a lithium secondary battery, method for manufacturing thereof, and lithium battery comprising the negative electrode

    KR1020230026219A